2005
DOI: 10.1063/1.1932664
|View full text |Cite
|
Sign up to set email alerts
|

Steady axisymmetric flow in an open cylindrical container with a partially rotating bottom wall

Abstract: Flow past a square cylinder with an angle of incidence Phys. Fluids 22, 043603 (2010); 10.1063/1.3388857Characteristics of two-dimensional flow around a rotating circular cylinder near a plane wallThe steady motion of a viscous fluid in a cylindrical container with a partially rotating bottom wall and a free surface is investigated by means of axisymmetric Navier-Stokes simulations. The flow above the spinning disk at the center of the bottom wall is dominated by an Ekman boundary layer that drives the fluid r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
37
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 22 publications
(18 reference statements)
8
37
0
1
Order By: Relevance
“…The Reynolds number for onset of vortex breakdown is between Re = 1000 and 1200, which is higher than that in the bioreactor without the scaffold (about Re = 500) [21]. In addition, the size of the vortex breakdown bubble is smaller than that in the bioreactor without the scaffold.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The Reynolds number for onset of vortex breakdown is between Re = 1000 and 1200, which is higher than that in the bioreactor without the scaffold (about Re = 500) [21]. In addition, the size of the vortex breakdown bubble is smaller than that in the bioreactor without the scaffold.…”
Section: Resultsmentioning
confidence: 98%
“…Since the Reynolds number was less than 1500, the Froude number Fr was negligibly small (in the order of 10 −3 ) and the free surface was assumed to be a flat stress-free surface. This assumption has been applied by other researchers to investigate the swirling flow in a chamber with a free surface [21]. The length and velocity components were scaled by 1/R and 1/( R), respectively.…”
Section: Governing Equations and Boundary Conditionsmentioning
confidence: 99%
“…Figure 2 shows the adhesion device in conjunction with the LSM. The device was built in such a way that the shaft can be moved towards and away from the glass bottom, in order for the arising convection current, described by Piva and Meiburg [27], not to interfere with the laminar boundary layer at the surface of the disc during rotation. In order to avoid spilling of the cell culture medium during the up and downward movement a rotary shaft seal was built into the lid of the measuring device.…”
Section: Methodsmentioning
confidence: 99%
“…The spinning disc setup has been studied extensively in the past and solutions for the calculation of the shear stress have been derived [27][28][29][30][31]. Garcia et al [2] suggested that once more than 50% of the cells at a given radial position are detached the experiment has been completed successfully.…”
Section: Methodsmentioning
confidence: 99%
“…In the limit of the knife edge radius being equal to the cylinder radius (A r → 1), for large Bo, we recover the flow in an enclosed stationary cylinder driven by a rotating endwall. 21 For larger A r , the flow is similar to a partially rotating endwall, 22 except that in that case, the azimuthal velocity beyond the edge of the rotating disk endwall is zero, whereas for our very viscous film, it is not zero and is given by v s = αr + β/r, as described in Sec. II.…”
Section: Resultsmentioning
confidence: 94%